The clash between the individualistic and the social concept of value - Barrington, Thomas (Statistical and Social Inquiry Society of Ireland, 1927)
It does not fall within the scope of this paper to review, however briefly, the respective merits of the various theories of value which have held or still hold the stage; rather is it proposed to indicate their inadequancy as criteria where the student or the statesman has to explore the bearings of economic phenomena not from the individualistic but from the social standpoint.
Read before the Society on Thursday, 7th April, 1927
Keywords: Human needs; Exchange of goods; 314.15